Assessment of comfort of living of the population of a municipality: methodological approaches - N. V. Fomina; A. M. Lugovskoy; B. I. Kochurov (Юг России: экология, развитие)
Aim. Testing of a methodological approach to the geo‐ecological assessment of the comfort of living in the territory of a municipality.Material and Methods. The study was conducted on the municipal administrative territory of the city of Balakovo in the Saratov region of the Russian Federation. The selection of accommodation comfort indicators has been based on a literature review. The degree of contribution of the selected indicators is determined by weighting factors of importance identified in the course of individual expert surveys. The ranking of results is based on converted values.Results. Five grades of comfort of living were determined for the population of Balakovo, The most comfortable neighborhoods are typically those of the older developed parts of the city, while the least comfortable are those of new neighborhoods adjacent to industrial zones.Conclusion. The following groups of indicators have been identified as having the greatest impact on levels of comfort of living in the municipality: environmental, urban planning, landscape and social. Each indicator was calculated quantitatively, taking into account the weight coefficients obtained based on the results of expert surveys.